Appointed time tracking control for marine surface vessels using the novel integral barrier function - Tan Zhang; Gang Zhang; Pianpian Yan; Jinzhong Zhang (Scientific Reports)
Abstract In this study, an appointed-time tracking controller is devised for the marine surface vessel based on the novel mathematical methods. The novel mathematical methods include that (i) a new high-order integral barrier function is proposed to deal with the symmetric and asymmetric constraints of the high-order systems; (ii) an appointed-time performance function is given to make the performance-constrained error converge to residual domains within the user-designated time; (iii) an integral term is introduced into the disturbance observer to improve estimation accuracy. The rationality of the proposed mathematical method has been proven through theorems. Finally, simulation experiments on a fully actuated surface vessel with three degrees of freedom are used to confirm the efficacy of the trajectory tracking controller developed using the high-order integral barrier function, appointed-time performance function, and disturbance observer.